A Research Paper on Green Marketing: Exploring the Growth and Impact of Green Marketing (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Green marketing is a phenomenon which has developed particular importance in the modern market. This concept has enabled for the re-marketing and packaging of existing products in eco-friendly material as per the guide lines. Additionally, the development of green marketing has opened the door of opportunity for companies to create a g-brand(co brand) brand of their products into separate line, lauding the green-friendliness of some while ignoring that of others. Such marketing techniques will be explained as a direct result of movement in the minds of the consumer market. As a result of this businesses have increased their rate of targeting consumers who are concerned about the environment. These same consumers through their concern are interested in integrating environmental issues into their purchasing decisions through their incorporation into the process and content of the marketing strategy for whatever product may be required.This paper discusses how it is a important for a aspect to fulfill their corporate responsibility and businesses have increased their rate of targeting green consumers, those who are concerned about the environment and allow it to affect their purchasing decisions. The paper also examines the present trends of green marketing in India and describes the reason why companies are adopting it and future of green marketing and concludes that green marketing is something that will continuously grow in both practice and demand.